Evaluating the Feed-in Tariff Policy in the Philippines - Lagac, Joyce Marie P (Archīum Ateneo, 2021)
To address the problems of climate change and energy security; the Philippines enacted the Renewable Energy (RE) Act of 2008. The law mandated the Feed-In Tariff (FiT) policy; which was designed to provide a guaranteed fixed price to RE investors for 20 years to develop renewable technology. This paper aims to evaluate the effectiveness of the FiT policy in promoting renewable energy development in the Philippines by assessing its costs and benefits. Data show that while the FiT has led to an increase in RE generating capacity; the share of renewable energy in the country has been declining since 2011. The findings also suggest that the Philippines has incurred a net social cost from its implementation of the FiT.